Pengembangan Sistem E-learning berbasis Perzonalisasi Ontologi - Bernard Renaldy Suteja; Suryo Guritno; Retantyo Wardoyo; Ahmad Ashari (UIN Sultan Syarif Kasim Riau, 2011)
Today, a form of technology known as Web 2.0 that thoroughly supports web-to-web interactions is present. Interactions, such as information sharing in the forms of document sharing (slideshare), picture sharing (flickr), video sharing (youtube), Wikis, and online networking (weblog and web-forum) are principally accommodating community empowerment services. These factors cause the appearance of social interaction through Internet as well as learning interaction and anywhere-anytime training which is recently called e-Learning. Basically, e-Learning needs a self-employed learning method and learning habits that emphasize on the learner as the most important role. However, e-learning system which is expected to boost the intensity of self-employed learning is incapable to represent the importance. This is proven with the current e-Learning system in Indonesia that only accommodates the delivery of learning materials identical to all active learners, ignores the cognitive aspects and does not offer any approach or experience of interactive self-learning and disregards the aspect of users’ ability to adapt. The proposed e-learning system which is Web 2.0-based utilizes ontology as the representation of meaning of knowledge formed by the learner. Kata kunci: adaptive e-Learning, e-Learning, ontology, personalization e-Learning